2020
DOI: 10.1016/j.bpj.2019.11.3387
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic View of Collective Filament Motion in Active Nematic Networks

Abstract: Protein filament networks are structures crucial for force generation and cell shape. A central open question is how collective filament dynamics emerges from interactions between individual network constituents. To address this question, we study a minimal but generic model for a nematic network in which filament sliding is driven by the action of motor proteins. Our theoretical analysis shows how the interplay between viscous drag on filaments and motor-induced forces governs force propagation through such i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…They are made of dynamic microtubules that are continuously transported towards the poles by molecular motors in a process known as poleward flux ( Mitchison, 1989, Maddox et al, 2002 ). In Xenopus laevis egg extract spindles, this flux depends on the activity of Eg5, a kinesin motor that can slides antiparallel microtubules ( Miyamoto et al, 2004, Kapitein et al, 2005, Uteng et al, 2008, Striebel et al, 2020 ). As a consequence, microtubule flows should depend on the spatial distribution of antiparallel microtubule overlaps in the structure.…”
Section: Introductionmentioning
confidence: 99%
“…They are made of dynamic microtubules that are continuously transported towards the poles by molecular motors in a process known as poleward flux ( Mitchison, 1989, Maddox et al, 2002 ). In Xenopus laevis egg extract spindles, this flux depends on the activity of Eg5, a kinesin motor that can slides antiparallel microtubules ( Miyamoto et al, 2004, Kapitein et al, 2005, Uteng et al, 2008, Striebel et al, 2020 ). As a consequence, microtubule flows should depend on the spatial distribution of antiparallel microtubule overlaps in the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion. -Commonly, the spatial self-organization of a filament arrangement is attributed to motor proteins that reorient and move filaments by mechanical forces, such as dynein or kinesin-5 [7,18,49,50]. Here, we have shown that microtubule length regulation (through kinesin-8) in combination with resource limitation can lead to aster-like spatial patterns.…”
mentioning
confidence: 73%
“…A somewhat related point has recently been made regarding heavily cross-linked networks of molecular motors and microtubules. An in vitro experiment on large aligned arrays of microtubules and kinesin-14 found that microtubules slide apart from each other at a speed that is independent of the local polarity of the network (i.e., the number of left vs. right facing microtubules), which would not occur if fluid drag forces on microtubules are significant [ 62 , 63 ]. A similar independence of microtubule sliding speed and polarity is seen in Xenopus egg extract spindles, arguing that fluid drag is also likely irrelevant for microtubule motions in those spindles.…”
Section: Mechanics and Its Relevance To Anaphase Spindlesmentioning
confidence: 99%